202 5-Aminolevulinic Acid-Induced Protoporphyrin IX Fluorescence in Low-Grade Gliomas. Issue Volume 61:Issue CN Supp. 1(2014)Supplement (1st August 2014) - Valdes, Pablo A.; Jacobs, Valerie L.; Harris, Brent T.; Wilson, Brian; Leblond, Frederic; Paulsen, Keith; Roberts, David W.
Abstract: INTRODUCTION: Fluorescence-guided resection using 5-aminolevulinic acid-induced protoporphyrin IX (ALA-PpIX) has shown promising results in high-grade gliomas. However, few studies have investigated the utility of ALA-PpIX in low-grade gliomas. We have previously shown significantly improved diagnostic performance in high-grade gliomas using a quantitative technique for fluorescence-guidance compared to state-of-the-art visible fluorescence imaging techniques. Here we present our initial experience using both visible, subjective fluorescence and quantitative fluorescence in low-grade gliomas. METHODS: Twelve patients with a diagnosis of low-grade glioma were administered 20 mg/kg of ALA prior to surgery under an institutional Review Board approved protocol. Assessments of the visible, red fluorescence and quantitative measurements of PpIX concentrations (CPpIX) were obtained from multiple locations intraoperatively, and subsequently biopsy specimens underwent neuropathological analysis. Receiver operating characteristic (ROC) analysis to assess the diagnostic performance of both fluorescence guidance techniques was performed. RESULTS: Five of 12 tumors demonstrated at least 1 instance of visible fluorescence. Normal tissue presented with a mean CPpIX = 51.0 ng/mL [min = 0.0, 25th-percentile = 1.0, 75th-percentile = 5.0, max = 567.0], while tumor had a mean CPpIX = 766.0 ng/mL [min = 0.0, 25th-percentile = 1.0, 75th-percentile = 177.0, max = 10540.0]. ROC analysis of visible fluorescence yielded a diagnostic accuracy of 38.0% (cut-off threshold = visible fluorescence score ≥1, AUC = 0.514), whereas quantitative fluorescence yielded a diagnostic accuracy of 67 % (for a cut-off threshold of CPpIX >5.6 ng/mL, AUC = 0.66). Further, 45% (9/20) of tumor specimens that were not visibly fluorescent, which would have otherwise gone undetected, accumulated diagnostically significant levels of CPpIX using quantitative fluorescence measurements. CONCLUSION: This initial experience of ALA-PpIX in LGG concurs with the literature understanding that visible fluorescence results in poor diagnostic accuracies. We found diagnostically significant levels of CPpIX in LGGs that were non-visibly fluorescent and below the visible fluorescence detection threshold. Further, in this initial experience using quantitative methods, we found that the diagnostic performance of ALA-PpIX in LGG approaches that of visible methods for high-grade gliomas.